Accompaniment of pedagogical action and learning: Core task of leaders in early childhood education (Pedagogical Horizons, 2022)
This article is dedicated to the task of managers in early childhood eucation to be responsible for the pedagogical processes and interactions at the institution.By means of group discussions with 10 kindergarten inspectors or consultants, the pedagogical events are inductively reconstructed and presented, with two leadership concepts (leading by values or leading by goals) serving to structure them. The qualitative data analysis shows that the supervision of the pedagogical activities of staff members is experienced as challenging by the managers, since they are not only responsible for the teaching-learning process in early childhood education, but also have a significant influence on the pedagogical quality. In addition to the many and complex tasks, they are attributed to lack the professional and leadership skills needed to manage and support pedagogical activities and learning in their institutions. This is closely related to the lack of qualifications of the managers, heterogeneous framework conditions and insufficient time structures.
Keywords: leading and managing; leadership action; educational action; paedagogical quality; paedagogical leadership